PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID “TAWAF EDU” PADA MATERI HAJI DAN UMROH DI MADRASAH ALIYAH - Nurani, Chamelia Bunga; Junaris, Imam (Institut Agama Islam Negeri Palangka Raya, 2025)
This study aims to develop and evaluate the feasibility of an Android-based instructional media, Tawaf Edu, for teaching Hajj and Umrah materials in Fiqh learning at Madrasah Aliyah. The research employed a Research and Development (R&D) approach, utilizing the ADDIE model, which encompasses the analysis, design, development, implementation, and evaluation stages. This study collected data through classroom observations, interviews, expert validation, and student trials involving small and large groups. Media experts, content experts, and students assessed the feasibility of the media using validated evaluation instruments. The results indicate that Tawaf Edu achieved high feasibility ratings from media experts (91%) and content experts (94%), categorized as highly feasible. Student trials also demonstrated positive responses, with feasibility scores of 85% in the small-group trial and 84% in the large-group trial. The integration of interactive ritual simulations, audio-visual explanations, and formative assessment features supports students' conceptual and procedural understanding of Hajj and Umrah practices. These findings suggest that Tawaf Edu is a pedagogically appropriate instructional medium for Fiqh learning in Madrasah Aliyah and can serve as a practical reference for the development of multimedia-based religious education media.